PENGELOLAAN DIVERSITAS KARYAWAN DALAM MEMBANGUN KEUNGGULAN KOMPETITIF - Sri Lestari (P4M STIE Putra Bangsa, 2015)
This article entitled management diversity of employees to develop competitive advantage. Currently the business world increasingly tight competition. The company increasingly hard in fighting over scarce resources and consumers. The competition took place at both levels local, regional, national and international level. Companies are able to compete will be the winner in the competition. In the face of environmental conditions that increasingly erratic company should be able to operate optimally, that by having the competitive edge. Diversity can give you an advantage for the company especially in serving customers who are also diverse. HUMAN RESOURCES company that came from many different backgrounds have the talent of individuals and different experiences so that it can give you different ideas and can serve a diverse market anyway. It is certain that the diversity of employees at a company many benefits, however it is not denied that the diversity also poses many challenges. human resources management should plan and manage their employees being multiform in such a way that would give maximum performance for the company .To create this company should apply the principle of total quality management and Total Quality Control in managing their employees.